Targeting inflammasome pathway by polyphenols as a strategy for pancreatitis, gastrointestinal and liver diseases management: an updated review - Nani, Abdelhafid; Tehami, Wafâa (Frontiers in Nutrition, 2023)
Obesity, pancreatitis, cardiovascular, gastrointestinal (GI), and liver diseases have all been linked to the Western lifestyle, characterized by increased unhealthy food consumption and decreased physical activity. Besides obesity and pancreatitis, many GI and liver diseases are associated with inflammation. Inflammasomes are multi-protein complexes that mediate acute and restorative inflammatory pathways. However, many aberrations in inflammasome activity originate from shifts in dietary habits. Evidence reveals that dietary polyphenols effectively modulate inflammasome-associated dysfunctions. With a focus on pancreatitis, GI, and liver disorders, this review set out to provide the most relevant evidence for the therapeutic impact of polyphenols via the regulation of the inflammasome pathway. Overall, flavonoid and non-flavonoid polyphenols maintain intestinal eubiosis, downregulate NLRP3 inflammasome canonical pathway, and restore redox status via upregulating Nrf2/HO-1 signaling. These effects at the level of the intestine, the liver, and the pancreas are associated with decreased systemic levels of key pro-inflammatory cytokines, including TNF-α, IL-1β, and IL-6.